Quantifying transmission electron microscopy irradiation effects using two-dimensional materials - Susi, Toma; Meyer, Jannik C; Kotakoski, Jani (Nature reviews physics, 2019)
Recent advances in transmission electron microscopy instrumentation have made it an indispensable technique for atomic-scale materials characterization. Concurrently, the availability of 2D materials has provided ideal samples in which each atom or vacancy can be resolved. New possibilities for the application of focused electron irradiation are being revealed, namely, the controlled manipulation of structures and even individual atoms. Evaluating the full range of possibilities for this method requires precise understanding of the electron–matter interactions, which is becoming feasible owing to advances in both experimental techniques and theoretical models. In this Perspective, we summarize the state of knowledge of the underlying physical processes on the basis of the latest results on 2D materials, with a focus on the physical principles of electron–matter interactions rather than material-specific irradiation-induced defects. Two-dimensional materials could provide the experimental guidance for the development of quantitative models applicable to a wide range of materials.Atomically precise measurements in 2D materials can be used to quantify the effects of energetic electron irradiation. In this Perspective, we discuss how understanding of electron–matter interactions can help to stimulate the development of quantitative models that are generalizable to a wide range of materials.